Gambaran Pengetahuan dan Sikap Ibu Tentang Makanan Bergizi pada Balita di Posyandu Mawar 2 Dusun Sanrangan Desa Jene’tallasa Kecamatan Pallangga Kabupaten Gowa - Suriati Sumarji; Muhamad Isnaini; Rudi Salam; Didin Wahyudi (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Early childhood is a golden period in a child's growth and development, during which adequate nutrition is essential for optimal physical and cognitive development. However, nutritional problems, particularly stunting, remain a serious challenge in Indonesia, including in Gowa District, South Sulawesi, which requires serious attention from various parties. The nutritional status of toddlers is greatly influenced by the knowledge and attitudes of mothers as the main decision-makers in meeting the nutritional needs of their families. Research Objective: to determine the knowledge and attitudes of mothers regarding nutritious food for toddlers at the Mawar 2 Health Center in Sanrangan Hamlet, Jene'tallasa Village, Pallangga Subdistrict, Gowa Regency. Research Method: this study used a descriptive method, with accidental sampling as the sampling technique. Research Results: The data analysis and research results are based on only 46 respondents. The respondents showed that most mothers were of productive age (20- 37 years old), had a high school education (65%), and were predominantly housewives (87%). In terms of knowledge, it was found that 93% of mothers had good knowledge and 7% had sufficient knowledge about nutritious food, with none having poor knowledge. The most significant result was that 100% of the 46 mothers had a positive attitude towards nutritious food for toddlers, indicating a very high level of awareness and acceptance in the village. Conclusion: After conducting this study, it can be concluded that the knowledge and positive attitudes of mothers at the Mawar 2 Health Center in Sanrangan Hamlet, Jene'tallasa Village, Pallangga Subdistrict, Gowa Regency are influenced by several factors such as education, occupation, age, and information obtained from counseling and the mass media.